Social support and coping among female foreign domestic helpers experiencing abuse and exploitation in Hong Kong - Choy, Chin Yung; Chang, Leanne; Man, Po Yee (Frontiers in Communication, 2022)
In Hong Kong, female foreign domestic helpers are hired to assist in household chores and care. This study examined the coping and support-seeking strategies that the workers use to tackle workplace difficulties. A mixed-method design that incorporated a face-to-face survey with 106 FDHs and 21 in-depth interviews was adopted. The results showed that most participants experienced some forms of abuse and exploitation. Verbal threats and time exploitation were the most common forms of abuse and exploitation respectively. Participants preferred emotion-based coping over problem-based coping, which was present in their acceptance of workplace conflicts as norms, avoidance of negotiation, and withholding. Their major sources of emotional support were religion and friends who also worked as FDHs in Hong Kong. Employers had the potential to fulfill the workers’ support needs, but they must take the initiative due to imbalanced power relations.